THE SUSTAINABILITY REPORT ON COMPANY VALUE IN THE SRI-KEHATI INDEX PERIOD 2019 -2021 - Bhuana, Kadek Wisnu (Universitas Trilogi, 2023)
The purpose of this study was to find out whether the disclosure of the sustainability report on economic, environmental, and social dimensions influences firm value. Disclosure of the sustainability report on economic, environmental and social dimensions only has an effect of 29.2 % of company value. Disclosure of the sustainability report on the economic dimension has a positive effect on the company value of the sri-kehati index in 2019 - 2021. Disclosure of the sustainability report on the environmental dimension has a positive effect on the company value contained in the sri-kehati index in 2019 - 2021. Disclosure of the social dimension of the sustainability report has a negative effect on value companies listed in the sri-kehati index for 2019 – 2021. Disclosure of sustainability reports on economic, environmental, and social dimensions only has a positive effect on company value. Keywords: Firm Value, Sustainability Report